What drives innovation? Causes of and consequences for nanotechnologies - Ingrid Ott; Christian Papilloud; Torben Zülsdorf (Hamburgisches WeltWirtschaftsInstitut (HWWI), 2008)
Nanotechnologies are expected to be the dominant general purpose technology of the next decades. Their market potential is immense and especially demand side arguments will have far reaching consequences for innovations. They may occur as increased miniaturization or via building completely new products, processes or services. Innovations in the field of nanotechnologies do not only affect productivity in downstream sectors but these feed back to nanotechnologies thereby inducing circles of continuing innovation. Demand for nanocomponents mainly arises by firms while private demand is assigned to final products, processes or services that are augmented by nanotechnologies. Due to the technology's controversial character, the consumer's attitude towards risk and technology affects private demand and this may either spur or hamper innovation. The paper aims to unravel how these complex interdependencies and feedback mechanisms affect overall innovation that is induced by nanotechnologies and how this on its part affects further improvements of nanotechnologies.
Keywords: O33; Z13; 330; general purpose technologies; controversial technologies; determinants of innovation